Ionic Liquid Crystals - Saielli, Giacomo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In this book we have collected a series of state-of-the art papers written by specialists in the field of ionic liquid crystals (ILCs) to address key questions concerning the synthesis, properties, and applications of ILCs. New compounds exhibiting ionic liquid crystalline phases are presented, both of calamitic as well as discotic type. Their dynamic and structural properties have been investigated with a series of experimental techniques including differential scanning calorimetry, polarized optical spectroscopy, X-ray scattering, and nuclear magnetic resonance, impedance spectroscopy to mention but a few. Moreover, computer simulations using both fully atomistic and highly coarse-grained force fields have been presented, offering an invaluable microscopic view of the structure and dynamics of these fascinating materials.